Prediction of long term deformation for balanced cantilever prestressed concrete segmental box girder - Noordin, Basir (2005)
Long term deformation may be expressed as the sum of the instantaneous, creep and shrinkage strain. Generally, long term deformation will affects the durability of concrete structures. Creep is responsible for excessive deflection at service loads and cause excessive chamber or shortening in prestressed concrete member. While shrinkage may cause slightly cracking, this could lead to durability failures. In prestressed concrete construction, in addition to causing increase in deflection, both creep and shrinkage cause shortening of the concrete which in turn cause shortening of the prestressing tendons and reduction in prestressing force. In the construction of prestressed concrete segmental box girder by balanced cantilever method, the long term deformation has to be predicted because the deflection due to creep and shrinkage is critical and will cause durability failures. Because of this, commercial computer software such as ADAPT Software and RM 2000 Software was generated to replace manual calculation so that the prediction of long term deformation can be made faster and efficient. But this available software is very expensive. As such a project entitled "Prediction of long term deformation for prestressed concrete segmental box girder" is carried out to generate new commercial computer software as alternative from available commercial software to predict long term deformation. The scope of the project is to determine short and long term deformation and generate new commercial computer software of the prestressed concrete segmental box girder. From the study, it is found that the SAB 2005 program can be used as new commercial computer software to predict short and long term deformation of balanced cantilever prestressed concrete segmental box girder. Therefore, it is hope that the outcome of this project will contribute a new technology for the betterment of construction industry in Malaysia.